Resin bond strength to a zirconia reinforced ceramic after different surface treatments - Donassollo, Tiago Aurélio (2009)
This study evaluated the microtensile bond strength between a composite resin a zirconia - reinforced alumina-based glass infiltrad ceramic after different ceramic surface treatments.Blocks (12mmx10mmx5mm^3) of a ceramic containing zirconia were fabricated, polished, and divided at random into seven groups, with each group receiving a different surface treatment.The adhesive system and composite resin were applied to the treated ceramic; these composite-ceramic blocks were stored in distilled water(37°) for seven days. At that point, they were cut along two axes two axes to produce specimens with a cross-sectional area of 1.0(+- 0.1)mm^2. The specimens (n=20) were loaded in tension in a universal testing machine with a cross-head speed of 0.5 mm/minute. The microtensile bond strengh values were calculated and statistically analyzed using ANOVA and Tukey's test(a=0.05).Among the seven groups, speciments with both a silica coating and a silane coupling agent showed the highest mean microtensile bond strength values. All specimens treated with 9.5% hydrofluoric acid failed during the cutting procedure; among all specimens, the majority of the failures were cohesive. A positive correlation was observed between the fracture type and the microtensile bond strength(r=0.63)